2007
DOI: 10.1302/0301-620x.89b6.18644
|View full text |Cite
|
Sign up to set email alerts
|

A computer model of the position of the combined component in the prevention of impingement in total hip replacement

Abstract: Dislocation remains a major concern after total hip replacement, and is often attributed to malposition of the components. The optimum position for placement of the components remains uncertain. We have attempted to identify a relatively safe zone in which movement of the hip will occur without impingement, even if one component is positioned incorrectly. A three-dimensional computer model was designed to simulate impingement and used to examine 125 combinations of positioning of the components in order to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 42 publications
2
24
0
1
Order By: Relevance
“…Femoral orientation is outside the scope of this study, but surgeons need to bear in mind the importance of the combined anteversion of the femoral and acetabular components. 9 Stem et al 15 suggested that the acetabular anteversion in males was 2.7˚ less than that in females. Our results support these findings, but a post hoc power analysis of the version data was 58%, indicating that more patients are required for us to be confident of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral orientation is outside the scope of this study, but surgeons need to bear in mind the importance of the combined anteversion of the femoral and acetabular components. 9 Stem et al 15 suggested that the acetabular anteversion in males was 2.7˚ less than that in females. Our results support these findings, but a post hoc power analysis of the version data was 58%, indicating that more patients are required for us to be confident of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral anteversion of the stem will be mainly determined by the shape of the proximal femur in uncemented stems, but can be altered by 10°–20° in cemented stems 63. To allow for a maximal impingement-free range of motion, the combined anteversion of the femoral stem and acetabular cup for a given cup inclination has to be evaluated 54636465. Overall, 40° ± 10° of cup abduction angle is advised together with a combined anteversion of approximately 40° 6667.…”
Section: The Acetabular Componentmentioning
confidence: 99%
“…Regarding the theoretical analysis, there have been several computer simulation studies investigating the appropriate CA range to avoid implant-on-implant impingement. 5,6,18,19 Based on the results of the computerized 3-D model analysis, Widmer et al 6 claimed that an optimal combination for positioning of both components was 20–28° of AV and 40–45° of inclination. In addition, they proposed the formula (cup AV + 0.7 stem AT) to calculate the CA value and defined the ideal value to be 37.3°.…”
Section: Discussionmentioning
confidence: 99%